Fatty Acid Binding Protein‐4 and Risk of Cardiovascular Disease: The Cardiovascular Health Study - Egbuche, Obiora (J Am Heart Assoc, 2020)
BACKGROUND: FABP‐4 (fatty acid binding protein‐4) is a lipid chaperone in adipocytes and has been associated with prognosis in selected clinical populations. We investigated the associations between circulating FABP‐4, risk of incident cardiovascular disease (CVD), and risk of CVD mortality among older adults with and without established CVD. METHODS AND RESULTS: In the Cardiovascular Health Study, we measured FABP4 levels in stored specimens from the 1992–993 visit and followed participants for incident CVD if they were free of prevalent CVD at baseline and for CVD mortality through June 2015. We used Cox regression to estimate hazard ratios for incident CVD and CVD mortality per doubling in serum FABP‐4 adjusted for age, sex, race, field center, waist circumference, blood pressure, lipids, fasting glucose, and C‐reactive protein. Among 4026 participants free of CVD and 681 with prevalent CVD, we documented 1878 cases of incident CVD and 331 CVD deaths, respectively. In adjusted analyses, FABP‐4 was modestly associated with risk of incident CVD (mean, 34.24; SD, 18.90; HR, 1.10 per doubling in FABP‐4, 95% CI, 1.00–1.21). In contrast, FABP‐4 was more clearly associated with risk of CVD mortality among participants without (HR hazard ratio 1.24, 95% CI, 1.10–1.40) or with prevalent CVD (HR hazard ratio 1.57, 95% CI, 1.24–1.98). These associations were not significantly modified by sex, age, and waist circumference. CONCLUSIONS: Serum FABP‐4 is modestly associated with risk of incident CVD even after adjustment for standard risk factors, but more strongly associated with CVD mortality among older adults with and without established CVD.